Relation of Adiponectin to Glucose Tolerance Status, Adiposity, and Cardiovascular Risk Factor Load. (27th December 2011) - Wolfson, N.; Gavish, D.; Matas, Z.; Boaz, M.; Shargorodsky, M.
Abstract : Objective . Adiponectin has anti-atherogenic and anti-inflammatory properties. We investigated the influence of adiponectin on glucose tolerance status, adiposity and cardiovascular risk factors (CVRFs). Design and Patients . Study consisted of 107 subjects: 55 with normal glucose tolerance (NGT) and 52 with impaired glucose regulation (IGR) who were divided into two groups: 24 subjects with impaired fasting glucose (IFG Group) and 28 patients with type 2 diabetes mellitus (DM Group). In additional analysis, study participants were divided into two groups, according to CVRFs: low and high risk. Measurements: Patients were evaluated for glucose, HbA1C, insulin, lipids, CRP, HOMA-IR and adiponectin. Measurements . Patients were evaluated for glucose, HbA1C, insulin, lipids, CRP, HOMA-IR and adiponectin. Results . Adiponectin was significantly higher in NGT group than in IFG (P = 0.003 ) and DM (P = 0.01 ) groups. Adiponectin was significantly, positively associated with HDL and inversely associated with glucose, HbA1c, ALT, AST, TG, HOMA-IR. Patients with higher CVRFs load have lesser adiponectin compared to patients with low cardiovascular risk P < 0.0001 ). Adiponectin was inversely associated with the number of risk factors (r = −0.430, P = 0.0001 ). Conclusions . Circulating adiponectin was significantly lower in subjects with different degree of IGR compared to subjects with normal glucose homeostasis. Adiponectin was significantly lower in high risk group than low risk group and decreased concurrently with increased number of CVRFs.